Analisis Penerapan PSAK 109 Mengenai Pelaporan Keuangan Akuntansi ZIS pada BAZNAS Kabupaten Tegal - Rufaidah Mar’atusholihah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of Statement of Financial Accounting Standards (PSAK) 109 concerning Accounting for Zakat, Infaq, and Sadaqah at BAZNAS Tegal Regency and to assess its level of compliance with the applicable standards. This research is motivated by the importance of transparency and accountability in the management of zakat funds as a form of responsibility to the public and stakeholders. The study employs a qualitative method with a descriptive approach through observation, interviews, and documentation studies of the institution’s financial statements. The results indicate that BAZNAS Tegal Regency has prepared its financial statements in accordance with the components required by PSAK 109, including the statement of financial position, statement of changes in funds, statement of changes in managed assets, statement of cash flows, and notes to the financial statements. In terms of distribution, presentation, and disclosure, the implementation of the standard has complied both formally and substantively. However, in the aspects of recognition and measurement, the implementation is not yet fully comprehensive, as there has been no realization of non-cash asset receipts and no impairment testing has been applied to non-cash assets. Overall, the implementation of PSAK 109 has been administratively well executed, but further strengthening is required in technical and procedural aspects to ensure more optimal, consistent, and comprehensive application in accordance with sharia accounting principles.